Effectiveness of Semmes Weinstein 10 gm monofilament in diabetic peripheral neuropathy taking nerve conduction and autonomic function study as reference tests - Suchitra Dube; Sandip M Hulke; Santosh L Wakode; Sagar Khadanga; Avinash E Thakare; Rajay N Bharshankar; Abhijit Pakhare (Journal of Family Medicine and Primary Care, 2022)
Context: Diabetic peripheral neuropathy (DPN) if detected early can reduce the burden on the health system and prevent the development of diabetic foot ulcers and amputation. Aim: To study the effectiveness of Semmes Weinstein 10 gm monofilament in detecting DPN taking nerve conduction studies (NCS) and autonomic function testing (AFT) as reference tests. Settings and Design: Observational and comparative cross-sectional study conducted in the Physiology department AIIMS, Bhopal in collaboration with the Medicine department of the institute. Methods and Material: A total of 72 diagnosed type-2 diabetes mellitus patients were examined using Semmes Weinstein 10 gm monofilament, DPN was confirmed using NCS (Nihon Kohden Neuropack XI machine) and autonomic neuropathy was confirmed using AFT (Ewing's battery and Power lab) with heart rate variability (HRV). Diagnostic value of Semmes Weinstein 10 gm monofilament taking NCS and AFT as reference test was calculated. Statistical Analysis Used: Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) were calculated using the standard formula. Results: Sensitivity, specificity, PPV, and NPV using monofilament are 69.23%, 20%, 69.23% and 20% respectively taking NCS as reference test and 70.59%, 0, 92.30%, and 0 respectively taking AFT as reference test. Conclusions: Semmes Weinstein 10 gm monofilament is not the ideal screening test for the diagnosis of DPN. Sole clinical use of monofilament should be discouraged.